Organ weights of three dolphin species (Sousa chinensis, Tursiops aduncus and Delphinus capensis) from South Africa: implications for ecological adaptation? - Plon, S.; Albrecht , K. H.; Cliff, G.; Froneman, P. W. (J. Cetacean Res. Manage., 2023)
Data from bycaught, but otherwise presumed healthy individuals can contribute important biological data on species of cetaceans that are otherwise lacking. This study utilises data collected from systematic necropsies performed between October 1970 and May 2010 on 142 Indo-Pacific humpback dolphins (Sousa chinensis), 607 Indo-Pacific bottlenose dolphins (Tursiops aduncus), and 640 long-beaked common dolphins (Delphinus capensis) incidentally caught and drowned in the shark nets off KwaZulu-Natal, South Africa. The aim of this analysis was to: (1) determine average absolute and relative organ weights for the three taxa as baseline values for later pathological examinations; and (2) examine potential correlations with the physiology and ecology in the three genera. Body length-weight relationships were described for the three species, indicating that S. chinensis is more robust than T. aduncus, with D. capensis being the smallest species out of the three taxa. Organ weights, as a percentage of total body weight were examined for the three delphinids. Organs examined included heart, lungs and trachea, liver, kidneys, spleen, and testes. Relative heart, liver and kidney weights were significantly larger in the small-bodied, fast-swimming D. capensis, than in the slower, more coastal S. chinensis and T. aduncus, possibly reflecting differences in activity patterns between the three species. Relative lung and trachea weights were not significantly different in the three species. Combined testes weight, as a percentage of total body weight, in combination with information on group size and sexual dimorphism suggested a monogamous or extreme polygynous (harem) mating system in S. chinensis, frequent copulations in T. aduncus, and sperm competition in D. capensis. The results of the present study suggest that the relative sizes of the major organs in the three genera are a reflection of the differing life histories and ecologies of the species examined.